Teacher Welfare Management and Its Implications for Improving Students' Numeracy Literacy in Indonesia: Literature Review - Hilda Nur Alifah Setyo Utami; Lailatul Inayah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Low achievement of Indonesian students in literacy and numeracy in PISA 2022 (359 and 366 points, far below OECD average of 476-493 points) demands evaluation of factors affecting learning quality. This study analyzes the relationship between teacher welfare management and improvement of student literacy and numeracy through systematic literature review of 44 studies covering 76,990 teachers from 2019-2025. Analysis shows significant relationship between teacher welfare and student academic achievement through three mechanisms: increased teaching efficacy, positive classroom climate creation, and pedagogical innovation development. International comparison reveals significant gaps between Indonesia and developed countries like Japan (teacher salary Rp38 million vs Indonesia Rp800,000-Rp2,000,000). Implementation in Indonesia faces challenges of regional disparities, employment status inequality, and excessive workload. Comprehensive policy reform is needed including compensation standardization, holistic support programs, and longitudinal studies to understand deeper causal mechanisms.